International Humanitarian Action NOHA Textbook (Springer International Publishing, 2018)
This textbook examines a wide range of humanitarian action issues in five parts, presented by specialists from different academic fields. The respective parts reflect the five core modules of the International NOHA Joint Master's Programme "International Humanitarian Action": a) World Politics, b) International Law, c) Public Health, d) Anthropology, and e) Management. The book serves as a common basis for teaching at all NOHA universities and aims at imparting the basic knowledge and skills needed to excel in a complex interdisciplinary and international learning context. It provides in-depth information on key international humanitarian principles and values, professional codes of conduct, and the commitment to their implementation in practice. The book will thus be useful for all students of the NOHA Joint Master's Programme and participants of any courses with a similar content, but also for academics and practitioners affiliated with entities such as inte rnational organisations and NGOs. It may also serve as an introduction to anyone with an interest in understanding the numerous and inter-linked facets of humanitarian action.